1999
DOI: 10.3171/jns.1999.91.6.0997
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced radiosensitivity of malignant glioma cells after adenoviral p53 transduction

Abstract: The ability to enhance the radiosensitivity of malignant glioma cells that express wild-type p53 by using adenoviral transduction to induce overexpression of p53 offers hope for this approach as a therapeutic strategy, not only in human gliomas that express mutant p53, but also in those that express wild-type p53.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…1 Tumor cells carrying p53 mutations are resistant to apoptosis induced by DNA damage, while an overexpression of wild-type p53 enhances the radiosensitivity of glioma cells. [33][34][35] However, the effect of p53 mutations on the efficacy of radio-and chemosensitivity in patients with gliomas, especially GBMs, remains controversial. Some have reported that the p53 status of GBM patients did not affect their survival 22,29 or p53 Mutations in Glioma/Shiraishi et al p53 Mutations in Glioma/Shiraishi et al…”
Section: Discussionmentioning
confidence: 99%
“…1 Tumor cells carrying p53 mutations are resistant to apoptosis induced by DNA damage, while an overexpression of wild-type p53 enhances the radiosensitivity of glioma cells. [33][34][35] However, the effect of p53 mutations on the efficacy of radio-and chemosensitivity in patients with gliomas, especially GBMs, remains controversial. Some have reported that the p53 status of GBM patients did not affect their survival 22,29 or p53 Mutations in Glioma/Shiraishi et al p53 Mutations in Glioma/Shiraishi et al…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the multimodality approach including radiation therapy is a common strategy for gliomas. Some reports have shown the advantage of additional radiation therapy to gene therapy, such as p53 gene 12,13 and ganciclovir (GCV ) /herpes simplex virus thymidine kinase ( HSV-TK ) prodrug /enzyme therapies. 14 -18 Additionally, combined therapy with 5-FC /CD treatment plus radiation was reported to have a therapeutic advantage compared to 5-FC /CD therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…12,17 Histological analysis of longitudinally surviving rats was not documented. Consequently, we were unable to compare brain alterations to the Kim and Broaddus data.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] The molecular basis of GBM resistance has not been fully elucidated. However, overexpression or amplification of epidermal growth factor receptor (EGFR), 6 PTEN and p53 mutations 7,8 and expression of PKC-Z 9 have been postulated to contribute to the lack of efficacy of chemotherapy and radiation in the treatment of GBMs and other cancers. Activation of EGFR stimulates a number of signal transduction pathways, including the Ras/Raf/mitogen-activated protein kinase (MAPK), Ras/PI3K/Akt/mTOR and PKC signaling pathways.…”
Section: Introductionmentioning
confidence: 99%